Kekuatan Tarik Komposit Hibrid Berpenguat Serat Batang Pisang Kepok Dan Serat Bambu Dengan Perlakuan Asap Cair - Rizki, Muhammad; Masdani, Masdani; Sugiyarto, Sugiyarto (Manutech : Jurnal Teknologi Manufaktur, 2025)
The development of technology every year has increased so rapidly. Current technology is developed in various new innovations. Due to the increasing use of metals reducing the availability of natural resources, therefore alternative materials that are environmentally friendly and renewable are needed. Technology in the field of materials, for example, natural fiber composites reinforced with kapok banana stem fiber and bamboo fiber. The purpose of this study was to determine how variations in the volume fraction of hybrid composites can affect the tensile strength of composite materials. Tests were conducted using the ASTM D638-1 standard. The analysis used a direct experimental design method. This study used variations in the volume fraction of kapok banana stem fiber: bamboo fiber 10%: 20%, 15% : 15%, and 20%: 10%. Liquid smoke soaking time is 2 hours. The average value of the tensile test is highest in the composition of kapok banana stem fiber: 10% bamboo fiber: 20% with an average value of 45.8 MPa, while for the lowest tensile test value in the composition of kapok banana stem fiber: 20% bamboo fiber: 10% with an average value of 42.1 MPa.